Motion compensation with skin contact control for high intensity focused ultrasound surgery in moving organs. (25th January 2018) - Diodato, A; Cafarelli, A; Schiappacasse, A; Tognarelli, S; Ciuti, G; Menciassi, A
Abstract: High intensity focused ultrasound (HIFU) is an emerging therapeutic solution that enables non-invasive treatment of several pathologies, mainly in oncology. On the other hand, accurate targeting of moving abdominal organs (e.g. liver, kidney, pancreas) is still an open challenge. This paper proposes a novel method to compensate the physiological respiratory motion of organs during HIFU procedures, by exploiting a robotic platform for ultrasound-guided HIFU surgery provided with a therapeutic annular phased array transducer. The proposed method enables us to keep the same contact point between the transducer and the patient's skin during the whole procedure, thus minimizing the modification of the acoustic window during the breathing phases. The motion of the target point is compensated through the rotation of the transducer around a virtual pivot point, while the focal depth is continuously adjusted thanks to the axial electronically steering capabilities of the HIFU transducer. The feasibility of the angular motion compensation strategy has been demonstrated in a simulated respiratory-induced organ motion environment. Based on the experimental results, the proposed method appears to be significantly accurate (i.e. the maximum compensation error is always under 1 mm), thus paving the way for the potential use of this technique for in vivo treatment of moving organs, and therefore enabling a wide use of HIFU in clinics.